The Comparison of the Total Body Mass between Pre and Postmenopausal Women in Mosul City - Majeed, Khalid Ghanim; Thanon, Husham A; Dhannoon, Basim Idrees; Fathi, Haitham B. (Iraqi Journal of Science, 2019)
In this research, we discussed bone density for women taking into consideration the method of research, we measure the total body mass of women in premenopausal and comparing it with postmenopausal, since the amount of the bone mineral content and bone mineral density, fat mass and lean mass.A cross sectional study conducted at DXA laboratory, Physiology Department, College of Medicine, University of Ninevah, Mosul-Iraq from Jan. 1 - Dec. 31, 2013. Since 174 healthy women recruited from reviewing of college medical academic center. They were divided into two groups: pre menopause group (n = 42) and post menopause group (n= 130). Detailed anthropometric data were gathered from study subjects. The mean age SD of pre-menopause group was (43.37 7.49) year while the mean age SD postmenopausal group (63.63 9.23) years .The T-score, Z-score, Bone Mineral Density (BMD), Bone Mineral Content (BMC), Fat Mass and Lean Mass were measured in the supine position by the use of DXA bone densitometer scanner type (STRATOS) from (DMS) group, France.Bone Mineral Content (BMC) was significantly lower in arm, rib, and thoracic spines. Bone Mineral Density (BMD) in arm, rib, leg and total were significantly low in postmenopausal women. Non-significant differences were noticed between both groups for lean mass. Postmenopausal women having more fat mass than pre menopause group. Both T-score and Z-score for pre menopause and post menopause groups were from class of osteopenia, but it was significantly lower in post menopause group (p-value =0.001, 0.008 respectively).Postmenopausal women were at higher risk of osteoporosis due to lowered Bone Mineral Density , T & Z scores.